Tindakan Wanprestasi Penyalahgunaan Keadaan oleh Developer Rumah pada Perjanjian Pengikatan Jual Beli: Studi Kasus Perkara No. 507/PDT/2017/PT.BDG - Adfari, Tsabitah Rahmah; Putri, Cinta Aisyah; Wicaksana, Dika Hikmah; Podungge, Khalisyah Amara; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Sale and Purchase Binding Agreement (PPJB) is a common instrument in property transactions in Indonesia, but is vulnerable to disputes, including acts of default and abuse of circumstances (misbruik van omstandigheden) by the developer. This normative legal research aims to analyse the forms of abuse of circumstances committed by developers in PPJB and the legal remedies that can be taken by aggrieved buyers. Using statutory, conceptual, and case study approaches (Decision No. 507/PDT/2017/PT.BDG), this research examines how developers can exploit their dominant position. The analysis shows that the developer's actions such as repeatedly delaying the handover of the unit despite the full payment, as well as filing a counterclaim against the buyer to avoid liability, can be categorised as an abuse of circumstances. These practices, which often take advantage of the imbalance of bargaining power, violate the principle of good faith and cause harm to consumers. Although not explicitly regulated in the Civil Code, this doctrine is relevant. The main remedy for buyers is through tort actions, demanding fulfilment of the agreement, compensation, or cancellation of the contract, where the argument of abuse of circumstances can strengthen the buyer's position in seeking justice.